2018
DOI: 10.3389/fevo.2018.00185
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Decline in Pathogen-Mediated Release of Methyl Salicylate Associated With Decreasing Vector Preference for Infected Over Uninfected Plants

Abstract: The Asian citrus psyllid, Diaphorina citri Kuwayama, is the vector of the phytopathogenic bacterium, Candidatus Liberibacter asiaticus (CLas), that causes citrus greening. Diaphorina citri is attracted to methyl salicylate (MeSA) emitted by CLas-infected citrus. MeSA is catalyzed from salicylic acid (SA) by salicylic acid methyl transferase (SAMT). In addition, salicylate hydroxylase, an enzyme that degrades SA and suppresses host plant defense, is unregulated in CLas-infected as compared with uninfected citru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…Previous studies have indicated that some plants can release b-caryophyllene after infection by some bacteria [27][28][29] and egg-surface bacteria can cause the fruit to rot [30]. Thus, we hypothesized that egg-surface bacteria might be involved in increasing b-caryophyllene in fruits.…”
Section: Concentrations In Fruitsmentioning
confidence: 95%
“…Previous studies have indicated that some plants can release b-caryophyllene after infection by some bacteria [27][28][29] and egg-surface bacteria can cause the fruit to rot [30]. Thus, we hypothesized that egg-surface bacteria might be involved in increasing b-caryophyllene in fruits.…”
Section: Concentrations In Fruitsmentioning
confidence: 95%
“…To collect the VOCs, a volatile collection trap with 30 mg HayeSep Q adsorbent (Volatile Assay Systems Rensselaer, NY, USA) was inserted in the pull tube [61,62]. Collections for each target plant were done for two hours during stable environmental conditions, over a period of four days in early December prior to heather flowering [63].…”
Section: Sampling Of Volatilesmentioning
confidence: 99%
“…Bacteria can activate signalling molecules, such as hydrogen peroxide (H2O2), salicylic acid, and jasmonic acid, which increase the expression of genes encoding key enzymes involved in β-caryophyllene biosynthesis pathways 63 . For citrus, emission of β-caryophyllene increased significantly in both recently and long-term Candidatus Liberibacter asiaticus -infected citrus compared with controls 64 . Similarly, apple trees infected by Candidatus Phytoplasma mali emitted more β-caryophyllene than healthy trees and were more attractive to a psyllid ( Cacopsylla picta ) vector 65,66 .…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have indicated that some plants can release more β-caryophyllene after infection by some bacteria 2527 , and egg-surface bacteria can cause the fruit to rot 28 . Thus, we hypothesized that egg-surface bacteria are involved in increasing β-caryophyllene in fruits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation